Effects of Homocysteine and Related Compounds on Prostacyclin Production by Cultured Human Vascular Endothelial Cells - Wang, Jian; Dudman, Nicholas P B; Wilcken, David E L (Thrombosis and Haemostasis, 1993)
Elevated plasma homocysteine is associated with an increased risk of intravascular thrombosis. Platelet aggregation and thrombosis are inhibited by prostacyclin produced by the vascular endothelium. Our aim was to investigate whether homocysteine and related metabolites inhibit endothelial prostacyclin production. We used a radioimmunoassay for 6-ketoprostaglandin-F1α to assay medium which had been in contact with confluent cultured endothelial cells. In medium containing 20% human serum, endothelial prostacyclin production was not specifically inhibited by homocysteine, S-adenosylhomocysteine or protein-bound homocysteine. Further, there was no consistent difference in prostacyclin production by cells cultured in medium containing sera from homocystinuria patients, compared with medium containing normal healthy sera. We conclude that vascular disorder in homocystinuria is unlikely to result from effects of homocysteine or related metabolites on endothelial prostacyclin production. By contrast, S-adenosylhomocysteine and protein-bound homocysteine specifically inhibited prostacyclin production by cells cultured in medium containing 20% fetal calf serum.